(untitled) (World Bulletin of Social Sciences, 2024)
The article examines the creation of jobs in the agriculture of Uzbekistan, employment in agriculture, and the impact on poverty reduction, since 80% of the low-income population of Uzbekistan live in rural areas. Measures of state support for creating jobs in the agro-industrial complex of Uzbekistan are being considered